Implementation Of The Bil Qolam Method In Learning Memory Of The Qur'an Juz 30 In Children At TPQ Madinatul Qur'an Rembang Pasuruan - Indrawati Indrawati; Ahmad Marzuki; Ali Mohtarom (Educare: Journal Educational and Multimedia, 2023)
Basically memorizing the Qur’an from an early age is very important, because at an early age memorization will be accepted easily and well received if it is well stimulated. One of the places for children to memorize the Qur’an is at the Qur’an is at TPQ institution. The selection of the method used in the process of memorizing the Qur’an greatly influnces the child’s ability. One of the menthods that can be implemented in memorizing the koran at TPQ institutions is the Bil Qolam menthod. This menthod is very effective when applied in the process of memorizing the al-Qur’an juz 30 in children. There are two objectives of this research namely; 1) To describe the application of the Bil Qur’an menthod in increasing the memorization of the Qur’an juz 30 in children at TPQ Madinatul Qur’an Rembang Pasuruan. 2) Tofind out what factors support and hinder the memorization of the Qur’an juz 30 in children at TPQ Madinatul Qur’an. The approach taken in this study is a qualitative approach, whish is descriptive in nature. The type of research used is field research. Data collection techniques used in this study were interview, observation and documentation. Testing the validity of the data using source triangulation and method triangulation. Analysis of the data from this study using data reduction, data reduction, data presentation, and drawing conclusions. The results of this study are 1) Implementation of the Bil Qolam method in increasing memorization at TPQ Madinatul Qur’an, namely teachers reading students listening, teachers reading students imitating, students reading teachers listening to readings. 2) The supporting factors of the Bil Qolam menthod in the process of memorizing students are basic abilities of students, competent teachers, a good family envitonment amd giving rewards. While the inhibiting factors are students who cannot read the koran and don’t even know hijaiyah letters, unfavorable environmental influences, lack of parental support, and finally the lack of adequate facilities and infrastructure.